Intimate Partner Violence and Sexual Agency in a Nationally Representative Sample of Women and Girls in the Philippines - Yoshioka, Emily (Journal of interpersonal violence, 2022)
This study examined the prevalence of intimate partner violence (Intimate Partner Violence) and its associations with sexual agency among women and adolescent girls in the Philippines. Data came from the 2017 Philippines National Demographic and Health Survey (DHS), a nationally representative, cross-sectional survey of women and girls ages 15?49. Participants included 11,727 women and girls who reported having a current male partner. Survey measures included three indicators of Intimate Partner Violence (physical, sexual, emotional), ability to refuse sex, ability to insist on condom use, perception that a husband/boyfriend can be justified in hitting or beating his wife/girlfriend, and sociodemographic characteristics. Descriptive and multivariable statistical analyses were conducted, with survey weightings used to account for the complex survey design. Overall, 23.9% reported Intimate Partner Violence in their current partnership (10.1% physical violence, 3.4% sexual violence, 19.0% emotional violence), 11.2% believed a husband or partner could be justified in hitting or beating their wife, 10.5% reported being unable to refuse sex with their partner, and 20.4% were unable to ask their partner to use a condom. In multivariable analyses, experiences of sexual (OR .68; 95% CI .50, .92), physical (OR .83; 95% CI .68, 1.02), and emotional violence (OR .69; 95% CI .58, .81) were associated with lower adjusted odds of being able to ask a partner to use a condom. When placed in the same model, emotional violence had the strongest association with lower odds of negotiating condom use with partner (OR .70; 95% CI .57, .85). Perception that a husband/boyfriend can be justified in hitting or beating his wife/girlfriend was associated with lower ability to refuse sex and ask a partner to use a condom. Findings indicate a need for further investment in interventions to prevent Intimate Partner Violence and support the sexual health and agency of women and girls who have experienced Intimate Partner Violence in the Philippines.